THE IMPLEMENTATION OF WEEKLY QUIZZES ON STUDENTS’ GRAMMAR ACHIEVMENT IN MAN 1 MAKASSAR - Fauzy Sehuddin (JURNAL VENUS, 2018)
Based on the research findings and discussion in the previous chapter, it can be concluded that the use of weekly quizzes improves the grammar achievement of the eleventh year students of MAN 1 Makassar in academic year 2017/2018. It can beseen from the significant difference score between pretest and posttest after giving the treatment.